Platinum-free, carbon-based materials as efficient counter electrodes for dye-sensitized solar cells. (22nd May 2018) - Widiyandari, Hendri; Prasetio, Adi; Purwanto, Agus; Subagio, Agus; Hidayat, Rachmat
Abstract: The electrocatalytic potential of carbon materials makes them the most viable candidate to replace Pt as a counter electrode (CE) in dye-sensitized solar cells (DSSCs). In this research, we report our study using graphite, CNT/graphite composite, CNT, and Pt-based CEs in DSSCs. The electrochemical impedance spectroscopy (EIS) measurement showed that the CNT-based CE (CNT-CE) has the lowest charge transport resistance ( R ct ) compared with graphite and the CNT/graphite composite. The photovoltaic performance measurement showed that the CNT-CE resulted in a short-circuit photocurrent density ( J sc ) of 3.59 mA·cm −2 whereas the Pt-based CE (Pt-CE) resulted in a J sc of 2.76 mA·cm −2 .